Shamanisms, Religious Networks and Empowerment in Indigenous Societies of the Americas - Laugrand, Frédéric; Crépeau, Robert R. (Anthropologica, 2015)
At the time of writing, the Truth and Reconciliation Commission (CVR 2015a, 2015b) has just submitted its damning report on the impact of residential schools on the Indigenous people and cultures of Canada. In this voluminous report, the commission states that one of the objectives of residential schooling was to destroy Indigenous spirituality and replace it with a better one. While Indigenous territory, language, culture and identity are inseparable from Indigenous spirituality and constitute the essential dimensions of a whole way of being, "the cumulative impact of the residential schools was to deny First Nations, Inuit, and Métis peoples their spiritual birthright and heritage. In our view, supporting the right of Indigenous peoples to self determination in spiritual matters must be a high priority.